2021
DOI: 10.3390/su13169475
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Smartphone Addiction, Parent–Child Relationship, Loneliness and Self-Efficacy among Senior High School Students in Taiwan

Abstract: This study explores the link between smartphone addiction in senior high-school students, parent–child relationship, loneliness, and self-efficacy on the basis of the theory of planned behavior (TPB) and social cognitive theory (SCT). A survey of 2172 students (1205 female students, 966 male students; mean age = 16.58 years, SD = 0.78) from 32 senior high schools in Taiwan was conducted. Moderation mediation analysis was performed using Model 14 of SPSS PROCESS-macro to test the hypotheses of this study. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 84 publications
2
12
1
Order By: Relevance
“…Social cognitive theory (SCT), proposed by Bandura [16], argues that intraindividual factors, external environment, and behavior interact with each other. Studies on mobile phone addiction have applied SCT [17][18][19]. In particular, Lian et al [17] considered parenting style as an environmental factor and virtue as a personal factor based on SCT.…”
Section: Social Cognitive Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Social cognitive theory (SCT), proposed by Bandura [16], argues that intraindividual factors, external environment, and behavior interact with each other. Studies on mobile phone addiction have applied SCT [17][18][19]. In particular, Lian et al [17] considered parenting style as an environmental factor and virtue as a personal factor based on SCT.…”
Section: Social Cognitive Theorymentioning
confidence: 99%
“…On the basis of SCT, Kara et al [18] regarded the duration of daily smartphone usage as an environmental factor and regarded loneliness and general anxiety as personal factors; their findings revealed that the duration of daily smartphone usage, loneliness, and anxiety all significantly affected mobile phone addiction. Cheng et al [19] considered the parent-child relationship as an environmental factor and loneliness and self-efficacy as personal factors based on SCT. Their results revealed that an improvement in the parent-child relationship reduced loneliness and mobile phone addiction and an improvement in self-efficacy reduced mobile phone addiction.…”
Section: Social Cognitive Theorymentioning
confidence: 99%
“…Excessive use of cellphone is also known to change brain chemistry [ 14 ]. Cell phone addiction is likely to affect an individual’s familial and societal relationships as they grow old and has potential to become a major public health problem [ 15 ]. College teachers are important and crucial change makers in the society as they have the responsibility in shaping life of youth and students.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, negative parenting leads to unstable affection between parents and children (23)(24)(25), and adolescents show compensatory responses like seeking support in the online space to relieve anxiety and negative emotions caused by deficiency and find psychological stability, ultimately increasing the risk of smartphone addiction (9,26). Previous studies on the relationship between parenting and adolescent smartphone addiction reported that positive parenting attitudes decreased adolescents' smartphone dependence, and as the attitudes became more negative, the adolescents were more likely to depend on their smartphones (27,28). Hence, it was hypothesized that parents' negative parenting attitudes would play a mediating role in the relationship between parents' and adolescents' smartphone addiction.…”
Section: Introductionmentioning
confidence: 99%